Comprehensive analyses of immune activity in COVID-19-vaccinated idiopathic pulmonary fibrosis patients - Maciejewska, Agata; Czernia, Piotr; Piotrowska-Mieczkowska, Magdalena; Wajda, Beata; Słomiński, Bartosz; Romantowski, Jan; Sudoł, Adam; Dąbrowska, Małgorzata; Górska, Lucyna; Smiatacz, Tomasz; Niedoszytko, Marek; Jassem, Ewa; et al. (Frontiers in Immunology, 2025)
Idiopathic pulmonary fibrosis (IPF) is a progressive and fatal disease, characterized by impaired wound repair, tissue remodeling and fibrosis. Immune system may participate in the development and progression of the disease as indicated by altered activity in IPF sufferers. This study investigates the immune response to the BNT162b2 COVID-19 vaccine in patients with IPF compared to healthy controls, with a particular focus on evaluation of antibody responses, interferon-gamma release, cytokine profiling and a broad panel of immune cell subpopulations. IPF patients without prior exposure to SARS-CoV-2 had undetectable levels of anti-N IgG antibodies, highlighting their lack of previous infection. After vaccination, IPF patients showed a significant increase in anti-S1 IgG and IgA antibodies, though their levels were lower compared to healthy controls and convalescent IPF patients. Additionally, IPF patients exhibited altered proportions of regulatory T cells (Tregs) and effector T lymphocytes (Teffs) before and after vaccination. Specifically, IPF patients had higher percentages of Tregs with a Th2 phenotype and Th17 Tregs, along with reduced proportions of Th1/17 Tregs. Teffs in IPF patients showed a decrease in Th1-like and Th2-like populations after vaccination. Moreover, IPF patients demonstrated elevated populations of cytotoxic T lymphocytes (Tc) before vaccination and increased levels of γδ Tc cells throughout the study. Alterations in cytokine profiles were also observed, IPF patients showed higher levels of IL-6 and IL-22 compared to healthy controls. These findings suggest a distinct immune response in IPF patients to the COVID-19 vaccine, characterized by differences in antibody production, T cell differentiation and cytokine secretion compared to healthy individuals.